Making the metaverse real - Tatiana Zalan; Paolo Barbesino (Digital Business, 2023)
Key stakeholders across different industries with competing visions, motivations and technology bets are investing significant financial resources in developing the building blocks of the metaverse. The purpose of this opinion piece aimed primarily at practitioners is to explore the key question: What is needed to make the metaverse real? What are the key uncertainties that must be resolved? We are motivated by shedding light on whether the metaverse is just a new marketing buzzword or a new transformative trend. We have identified six areas with key uncertainties, which require agreement and solutions from industry players - the space, the interface, the IT infrastructure, the monetary infrastructure, the digital ID and the energy. These uncertainties will be resolved in a series of cooperative and competitive games among the key stakeholders who will need to work on being aligned on a set of standards. The practical implication is that the metaverse cannot be ignored, but there are non-trivial challenges that need to be resolved first. Our paper provides a framework for practitioners to think through these issues in a more systematic fashion.
Keywords: 650; Augmented reality; Digital ID; Internet; IT infrastructure; Metaverse; Virtual reality; Virtual worlds; web3